EFFECTS OF EXPOSURE TO MASS MEDIA MESSAGES ON TEENAGE VEILED PERCEPTIONS - Ridwan Rustandi; Khoiruddin Muchtar (INJECT (Interdisciplinary Journal of Communication), 2019)
The purpose of this study was to determine the impact on the soap opera Aisyah Putri that aired on the private television station RCTI. This study uses a qualitative approach by relying on George Gebner's theory of states that television shows affect the audience. Data collection techniques through observation and interviews are three main aspects, namely cognitive, affective and conative, related to the effects of exposure to mass media messages. Female students of Al-Biruni High School in Bandung consisting of classes X, XI, and XII. The results of the study showed that the process of perception of teenagers on Aisyah Putri soap opera shows the stages of sensation, perception, and confirmation (memory and thinking). The motive for the use of headscarves for teenagers. The headscarf perception among adolescents, especially for students at Albiruni Cerdas Mulia Bandung High School has a strong influence on exposure to "Aisyah Putri" religious soap operas in terms of cognitive, affective and conative.